Physicochemical analysis, antioxidant activity, and hedonic evaluation of facial serum containing roselle (Hibiscus sabdariffa) and pomegranate (Punica granatum) extracts - Adi Permadi; Yatus Widiana Hanizatul Ardila; Nanik Trijayati; Mutiara Wilson Putri; ABM Helal Uddin (Journal of Halal Science and Research, 2026)
The utilization of natural ingredients in cosmetic applications is increasing due to public awareness of their safety and minimal side effects. This study aims to evaluate and compare the antioxidant activity of facial serums containing Hibiscus sabdariffa (roselle) and Punica granatum (pomegranate) extracts. Physical quality tests were conducted, including organoleptic, homogeneity, pH, specific gravity, and viscosity evaluations. Organoleptic observations showed both formulations had stable characteristics, including brown color, typical herbal aroma, and thick consistency without changes during storage. Homogeneity testing indicated no phase separation or sedimentation. The specific gravity of both serums was 1.02 g/mL, meeting SNI standards. Viscosity values were 2840 cps for roselle serum and 2540 cps for pomegranate serum, indicating appropriate consistency for topical use. The pH values were 3.75 ± 0.006 and 3.94 ± 0.017, respectively. Antioxidant activity was analyzed using the DPPH method. IC₅₀ values were 6000 ppm for roselle extract and 359.163 ± 0.437 ppm for pomegranate extract, indicating very weak antioxidant activity for anti-aging applications. This low activity may be influenced by extract concentration, degradation during formulation, storage conditions, and environmental exposure. While both serum formulations successfully met the SNI 19-4339-1996 physical quality requirements for topical use, their antioxidant efficacy was insufficient for potent anti-aging applications. This study contributes a critical baseline for natural serum formulation, identifying that physical stability does not guarantee antioxidant potency. These findings provide a necessary foundation for future research to focus on optimizing extract concentrations and stabilizing bioactive compounds against degradation during the formulation process. Keywords: Antioxidant activity, DPPH assay, Facial serum, Pomegranate extract, Roselle extract.